Cost-effective hole transporting material for stable and efficient perovskite solar cells with fill factors up to 82%. Issue 44 (1st November 2017) - Guan, Lei; Yin, Xinxing; Zhao, Dewei; Wang, Changlei; An, Qiaoshi; Yu, Jiangsheng; Shrestha, Niraj; Grice, Corey R.; Awni, Rasha A.; Yu, Yue; Song, Zhaoning; Zhou, Jie; et al.
Abstract : A cost-effective truxene-based hole selective material has been facilely synthesized for efficient perovskite solar cells with 82% FFs. Abstract : A new small molecule-based hole selective material (HSM), 4, 4′, 4′′-(7, 7′, 7′′-(5, 5, 10, 10, 15, 15-hexahexyl-10, 15-dihydro-5 H -diindeno[1, 2- a :1′, 2′- c ]fluorene-2, 7, 12-triyl)tris(2, 3-dihydrothieno[3, 4- b ][1, 4]dioxine-7, 5-diyl))tris( N, N -bis(4-methoxyphenyl)aniline) (TRUX-E-T), has been developed by a facile synthesis with reduced cost. The highest occupied molecular orbital energy level and lowest unoccupied molecular orbital energy level of TRUX-E-T are −5.10 and −2.50 eV, respectively, making it a suitable HSM for lead iodide perovskite solar cells. TRUX-E-T can be smoothly deposited onto perovskite layers, enabling efficient perovskite solar cells with thin TRUX-E-T layers (∼50 nm), which helps cut the unit cost of the HSL used in PVSCs to approximately one-fortieth (1/40) of 2, 2′, 7, 7′-tetrakis ( N, N -di- p -methoxyphenylamino)-9, 9′-spirobifluorene (spiro-OMeTAD). Additionally, TRUX-E-T exhibits hole mobilities as high as 2.47 × 10 −4 cm 2 V −1 s −1, better than spiro-OMeTAD. As a result, our perovskite solar cells using TRUX-E-T have shown high fill factors up to 82%. The champion cell achieved a maximum power conversion efficiency of 18.35% (16.44%) when measured under reverse (forward) voltage scan under AM1.5 G 100 mW cm −2 illumination. Our un-encapsulated cells exhibited good stability in ambient air, maintaining 96.4% of their initial efficiency of 18.35% after 20 days of storage.